Credit and banking Component of the Market Economy Phenomenon: Methdological Approach Transformation to the Development of Digitalization and Capital Fictivization - Y. S. Yadgarov; V. A. Sidorov; E. V. Sobolev (Финансы: теория и практика)
The article is based on the results of the 7th International Scientific and Practical Conference on Economics “The Market Economy Phenomenon: From the Origins into Our Days” held from March 27 to March 31, 2019 in the cities of Sochi and Sukhumi. The theoretical approaches of domestic and foreign researchers to understanding the market economy phenomenon, the specifics of its financial and credit sphere functioning in the context of the digital economy were generalized. The problems of the monetary economy in terms of the sanction confrontation were outlined. The authors analyzed and evaluated the processes and the phenomena observed in the post-Soviet economic space related to the transplantation of market economy mechanisms into the system of social reproductive relations, including its financial component based on their digitalization. The dialectic approach, system analysis, methods of economic and statistical and interdisciplinary analytical tools were used. The article revealed the key components of the market economy phenomenon appearing in the post-Soviet economic space and having a direct impact on the social reproduction results. The relationship was shown between the transformation of the evolutionary and methodological content of the money economy, its institutional and behavioral paradigm, the digitalization of the financial segment of the economic space with the scale of innovation, the penetration of cognitive psychology and neurophysiology into financial and credit relations, and their technological re-equipment. The results of the influence of instability factors on the budget and monetary sphere were presented. The authors described complex interdependencies of the processes and phenomena within the framework of the market economy phenomenon appearing in the post-Soviet economic space. The triune structure of the modern market doctrine was disclosed including psychological and behavioral, institutional and functional and reproduction and product aspects. The authors showed the transformational dynamics of the financial and credit sphere of modern society. Its specific features are: the increasingly important role of innovation, outsourcing, revising pricing methods, digitalization of business processes, penetration into managing neuromarketing technologies, and virtualization of the financial sector of the economy.